PENERAPAN KAPITALISASI SEWA OPERASI TERHADAP LAPORAN POSISI KEUANGAN DAN RASIO KEUANGAN PADA PERUSAHAAN DI INDONESIA - Ayunita Ajengtiyas Saputri Mashuri (Pusat P2M Politeknik Negeri Batam, 2021)
The purpose of this study is to analyze the impact of capitalization on operating leases based on the latest accounting standards, namely PSAK 73 which is applicable in the preparation of financial reports related to lease activities. The impact of the convergence of PSAK 73 application of IFRS 16 introduces a single accounting model that applies to the lessee party, while for the lessor there is no difference with the previous standard. The type of research used in this research is quantitative research with the data used is secondary data by utilizing the data available in the annual reports and financial reports of companies listed on the Indonesia Stock Exchange, the period 2018-2019. Secondary data is taken by pulling company data that reveals the value of the future minimum lease payments regarding the operating lease in the company's financial statements. The research sample used in this study is a company listed on the Indonsia Stock Exchange in the 2018-2019 period, with the criteria that the company states that the type of lease transaction is an operating lease and provides information on the minimum value of lease payments in the future. The constructive capitalization lease method was developed by Imhof, et al. (1991). Data analysis methods include descriptive statistical testing and Paired T-Test and Anova test using the Minitab 16 statistical application software. The results of this study indicate that operating lease capitalization has a significant effect on unrecorded lease liability, unrecorded lease assets, equity, and financial ratios. . Also, empirical evidence shows that there are tax savings from capitalizing operating leases